Efektivitas (RPOA) Regional Plan of Action Dalam Penanggulangan IUU Fishing Studi Kasus: Penyulundupan Ilegal Benih Lobster Indonesia ke Vietnam - Faisal Adhiatma; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Lobster is an animal that has a lot of nutrition and has a high price because it is classified as an animal that is difficult to catch and only lives in the deep sea. So many benefits are produced from one Lobster that makes it much sought after connoisseurs of Lobster. Indonesia with its vast sea area makes the potential as the largest Lobster seed producer and exported to countries in Southeast Asia. But this was exploited by irresponsible parties by smuggling lobster seeds from Indonesia abroad in large numbers. The illegal practice continues, although the Government of Indonesia through a joint team continues to intensify the hunt for the perpetrators of the smuggling of this valuable marine biota. This research wants to explain the smuggling of Lobster seeds into various countries using the Green Theory approach. Specifically research uses the concept of Human Centered. This research argues that the government has been cheated by the practice of smuggling Lobster seeds, in this case the state is obliged to protect what is contained in the Indonesian territory is the full ownership of the state because it is a crop which is also contained in the law.